2012
DOI: 10.1177/1941874412459333
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Brain Lesions in a Renal Transplant Patient

Abstract: Neurologists should be familiar with the spectrum of central nervous system (CNS) pathology that renal transplants patients are prone to. We are presenting a case of posttransplant lymphoproliferative disorder of the CNS to highlight less commonly described imaging findings and review this disease entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Lesions contacting the meningeal and ependymal surfaces have also been reported [2 , 3 , 43] . Moscato et al reported a rare case of leptomeningeal predominant PCNS-PTLD lesions [13] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesions contacting the meningeal and ependymal surfaces have also been reported [2 , 3 , 43] . Moscato et al reported a rare case of leptomeningeal predominant PCNS-PTLD lesions [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic deficits have been reported in many cases, and include gait ataxia, dysarthria, and hemiparesis [2 , 6 , [8] , [9] , [10] . Facial nerve palsy has been reported in a few isolated cases [11] , [12] , [13] . PCNS-PTLD is most frequently diagnosed in patients with a history of SOT or HSCT, with renal transplants being the most predominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis includes PCNS lymphoma, glioblastoma (GBM), metastatic disease, abscess, or other infection. Infections in transplant patients can include Aspergillus, Nocardia asteroides, Toxoplasma gondii, Listeria monocytogenes, Mucorales, Tuberculosis, and less commonly Cryptococcus [24]. Less likely differential diagnostic considerations are tumefactive demyelination, stroke, or neurosarcoidosis.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…By detecting the EBV and cellular microRNAome in PTLD (Forte et al, 2012; Harris-Arnold et al, 2015), studies showed that there are two different microRNA profiles identified in primary central nervous system post-transplant lymphoproliferative disorders (pCNS PTLD). First, EBV microRNAs interacts with the cellular microRNAome similarly to that of EBV-associated systemic PTLD and the second could be limited to the immunological functions associated with the central nervous system (Moscato et al, 2013; Fink et al, 2014). Although, a limited expression of latency genes is also seen in EBV associated systemic PTLD, based on promoter utilization it is still considered to be latency III (Fink et al, 2014).…”
Section: Ebv Associated Diseasesmentioning
confidence: 99%